Nilai Perusahaan: Leverage, Profitabilitas, serta Ukuran Perusahaan - Wiwi Idawati; Irfan Faqih (Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This seacrh to eximine the effect of leverage, profitability, firm size of firm value. The population in this study is manufacturing companies listed on Indonesia Stock Exchange (IDX) in 2017-2019. The sample method use purposive sampling technique and the result 57 companies were obtaining with 93 observation; however, there are some outlier data that must be issued to obtain data normality assumption. Finally, there are 31 companies and 93 observations that can be as research samples. Hypothesist testing in this search uses fix effect model and multiple regression analysis. The test result obtaining that leverage has no negative effect on firm value, profitability has no positive effect on firm value, firm size has positive effect on firm value in companies listed on Indonesia Stock Exchange (IDX) in 2017-2019.